Upaya Penanganan Pasien Skabies Usia 23 Bulan Melalui Pendekatan Kedokteran Keluarga di Puskesmas Simpang Keuramat - Danisa Indira Fatma; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
A 23-month-old female patient presented with red, itchy bumps, accompanied by intense itching, which caused the skin to peel from scratching. These symptoms began less than a month before the visit and worsened one week before seeking treatment. The fluid-filled bumps burst due to scratching, causing sores and peeling skin. The itching was constant and tended to worsen at night. The use of moisturizer by the patient's mother provided little relief. The onset of these symptoms coincided with a visit from the patient's mother's younger brother, a student at the Islamic boarding school (Santri), who was staying at the patient's home during the holidays. Less than a month later, similar symptoms began to be felt by the patient, her siblings, and both parents. The diagnosis was based on primary data obtained through a history taking with the patient's mother, a direct physical examination during a home visit, and completion of the family file and the patient's medical records. The patient, suspected of having scabies, was treated with 5% permethrin cream, applied as directed, and cetirizine to reduce the itching. Case assessments are conducted holistically, assessing the initial condition, process, and final outcome of each visit both quantitatively and qualitatively. Interventions include not only treatment but also comprehensive family education. This education includes an explanation of the etiology and transmission of scabies, the importance of maintaining personal and environmental hygiene, and potential complications such as secondary skin infections due to scratching. The goal of this education is to improve patient and family compliance with therapy, prevent reinfection, and break the chain of disease transmission in the home environment. This approach is expected to not only reassure the patient but also raise family awareness of the importance of clean and healthy living practices as a long-term preventative measure.